Decentralization for development experiments in Bangladesh - Akhter, Muhammad Yeahia (Philippine Journal of Public Administration, 1990)
Like many other Third World countries, the successive governments in Bangladesh after gaining independence, adopted several decentralization policies as their primary tools in the development of the rural population. The Mujib Government (1972-1975) which inherited a strong centralized administration from Pakistan, introduced changes largely limited to a redefinition in the nomenclature of components of local administration. The Zia Government (1975-1982) on the other hand, introduced a scheme called self-reliant village government which ironically depended on the central government for its survival. The present Ershad Regime (1982-present) gives emphasis on administrative decentralization through the creation of upazilas in the hope that the condition of the rural folks would improve.